Colour Measurement and Mixture - Abney, William de Wiveleslie, Sir (E. & J. B. Young & Co., 1891)
Part of the Romance of Science Series, this volume provides an expanded version of a lecture series given by the author, Sir William de Wiveleslie Abney (1843-1920) at the Royal Society of Arts. Contents include sixteen chapters detailing the physical and chemical properties of visible light, color theory, and methods of measuring light. Work is illustrated with various spectra and depictions of instrumentation. It is digitized in its entirety.
Keywords: Colors; Color--Study and teaching; Spectrum analysis; Absorption spectra; Light